Meningoencephalitis following Le Fort I osteotomy: a case report. Issue 12 (December 2022) - Goh, R.; Beech, N.; Borgna, S.; Mansour, M.; Alexander, T.; Breik, O.
Abstract: Le Fort I osteotomies, although they are common procedures, carry a degree of risk of injury to the surrounding structures. Skull base fractures and cerebrospinal fluid rhinorrhoea are amongst the most serious on the list of complications. This is the first reported case of meningoencephalitis post Le Fort I osteotomy, shedding some light on its identification, causes, and management.